Strategic Management Analysis of the Halal Certification Program Implementation in Surabaya - Muhammad Yazid; Ismatul Khayati; Aji Prasetyo (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
This study aims to analyze the strategic management process in implementing the halal certification program by the Ministry of Religious Affairs of Surabaya City. The research specifically focuses on evaluating the alignment between policy formulation and local implementation using four analytical dimensions: consistency, consonance, advantage, and feasibility. A qualitative descriptive approach was employed through in-depth interviews, direct observations, and document analysis involving halal facilitators (P3H), ministry officials, and MSME representatives. The findings reveal that while the Surabaya City Office of the Ministry of Religious Affairs has aligned its operations with the national halal certification strategy established by BPJPH, challenges persist in stakeholder participation, resource adequacy, and digital integration. The study highlights that consistency and institutional advantage are relatively strong, whereas consonance and feasibility require reinforcement through clearer coordination and performance-based incentives. Theoretically, this research contributes by integrating Islamic ethical principles—amanah (trust), ihsan (excellence), and maslahah (public welfare)—into the framework of strategic management, thus providing a holistic model for public-sector halal governance and offering practical implications for improving local policy implementation and institutional performance.